Monetary Policy Dynamics in the Digital Era: Its Impact on Economic Growth and Global Market Stability - Efendi Efendi (Majapahit Journal of Islamic Finance and Management, 2026)
Monetary policy in the digital era faces new challenges such as market volatility, cyber security risks, and uncertainty regarding the effectiveness of traditional instruments. Technological transformations, including digital currencies and fintech, are reshaping economic dynamics, demanding faster policy adaptations. The research aims to describe the dynamics of monetary policy in the digital era and its impact on economic growth and global market stability. This study employs library research as its methodology. Primary data sources for this research include books, scientific journal articles, and published research reports. The research findings indicate that: 1) Digital Transformation and the Effectiveness of Traditional Monetary Policy Instruments show that digital transformation has reduced the effectiveness of traditional monetary instruments like interest rates and open market operations. The emergence of digital currencies and fintech has altered the circulation of money, leading to traditional policies being less effective in controlling inflation and economic growth. 2) The Impact of Digital Monetary Policy on Global Market Stability reveals that digital monetary policies, such as CBDCs, have the potential to enhance global market stability but also carry risks of volatility and cyber security. The speed of digital transactions can increase volatility, while cyber-attacks threaten stability. Central banks need to strengthen regulations and cyber security systems to mitigate these risks. 3) Digital Monetary Policy and Inclusive Economic Growth suggest that digital monetary policies can promote inclusive and sustainable economic growth, especially in developing countries. However, disparities in technology access among nations pose a primary challenge.